Pedunculopontine nucleus stimulation for gait and postural disorders in Parkinson's disease - Thevathasan, AW (2011)
The pedunculopontine nucleus (PPN) is a reticular collection of neurons at the junction of midbrain and pons. The PPN in animal models appears topographically organised and functionally related to locomotion and arousal. In Parkinson’s disease, the PPN degenerates and is susceptible to abnormal basal ganglia output. In patients with Parkinson’s disease, low frequency PPN stimulation is proposed to improve gait freezing and postural instability. However, the therapeutic mechanisms, optimal clinical application and precise effects on gait and posture of PPN stimulation are unclear. Here, a topographic arrangement of the PPN was supported by local field potential recordings in parkinsonian patients. In the PPN region, beta oscillations were recorded rostrally and alpha oscillations caudally. Alpha oscillations, consistent with their putative role in allocating attention, correlated with gait performance and attenuated with gait freezing. Thus the caudal PPN subregion may be the most relevant target for gait disorders. Accordingly, an unblinded clinical study suggested that stimulation of the caudal PPN subregion was beneficial for gait freezing, postural instability and falls. In a double-blinded study using spatiotemporal gait analysis, caudal PPN stimulation reduced triggered gait freezing, with bilateral stimulation more effective than unilateral. However, akinesia including akinetic gait did not improve with PPN stimulation. Accordingly, dopaminergic medication requirements did not change. Mechanisms underlying gait freezing and PPN stimulation were explored with reaction time experiments. Parkinsonian patients with severe gait freezing and postural instability demonstrated a ‘block’ to pre-programmed movement. This was evidenced by prolonged simple reaction times and the absence of ‘StartReact’, whereby pre-prepared responses are normally accelerated by loud acoustic stimuli. PPN stimulation improved simple reaction time and restored Startreact. The relief of this ‘motor block’ with PPN stimulation may therefore explain the associated improvement in gait freezing and postural instability, as these tend to occur in circumstances requiring triggered, pre-prepared adjustments.